Bridge design, construction and maintenance : proceedings of the two day international conference organised by the Institution of Civil Engineers and held in Beijing on 17-18 September 2007 - Lark, Robert (Thomas Telford Publishing, 2007)
Bridge engineering requires an innovative, multi-disciplinary approach built on a sound foundation of experience and research. ICE organised an international conference on current and future trends in bridge design, construction and maintenance.